Efforts to provide digital literacy in school library SDIP Ummul Mukminin - Salwa Khairunnisa; Hafsah Nugraha (Himpunan Pengembang Kurikulum Indonesia, 2026)
The rapid development of digital technology requires school libraries to play an active role in strengthening students’ digital literacy. This study aims to examine how school libraries enhance students’ digital literacy amid the rapid growth of information technology. This research adopts a qualitative approach using an intrinsic case study method conducted at SDIP Ummul Mukminin, Bandung. Data were collected through comprehensive interviews with librarians and educators, as well as direct observation of the library’s conditions. The findings indicate that digitalization efforts have begun through the provision of computer facilities and digital learning modules. However, digital transformation has not yet been implemented optimally, as collection management and circulation services are still conducted manually and are not supported by digital collections, such as e-books and interactive learning platforms. In addition, students’ digital literacy is strengthened through the integration of Islamic values and ethical principles taught by teachers and librarians. This study emphasizes that the development of digital libraries requires the contextual integration of technology, the enhancement of librarians’ competencies, the diversification of digital collections, and a sustained commitment from all school stakeholders. Abstrak Perkembangan teknologi digital menuntut perpustakaan sekolah untuk berperan aktif dalam mendukung penguatan literasi digital murid. Penelitian ini bertujuan untuk mengetahui bagaimana perpustakaan berperan dalam memperkuat kemampuan literasi digital murid di tengah pesatnya perkembangan teknologi informasi saat ini. Penelitian ini menggunakan pendekatan kualitatif dengan metode penelitian studi kasus intrinsik di SDIP Ummul Mukminin, Bandung. Pengumpulan data dilakukan melalui wawancara komprehensif bersama pustakawan dan tenaga pendidik, serta observasi langsung terhadap kondisi perpustakaan. Temuan penelitian menunjukkan bahwa upaya digitalisasi telah mulai dilakukan melalui penyediaan fasilitas komputer dan modul digital. Namun, transformasi digital belum berjalan secara optimal karena pengelolaan koleksi dan layanan peminjaman masih dilakukan secara manual serta belum didukung oleh ketersediaan koleksi digital seperti e-book dan platform pembelajaran interaktif. Selain itu, literasi digital pada murid diperkuat dengan penanaman nilai-nilai dan etika keislaman yang diajarkan oleh guru dan pustakawan. Penelitian ini menegaskan bahwa pengembangan perpustakaan digital memerlukan integrasi teknologi yang kontekstual, peningkatan kompetensi pustakawan, diversifikasi koleksi digital, serta komitmen berkelanjutan dari seluruh pemangku kepentingan sekolah. Kata Kunci: integrasi teknologi; literasi digital; perpustakaan sekolah dasar